The association between Geriatric Nutritional Risk Index and KSD disease: results from National Health and Nutrition Examination Survey 2007–2018 - Tang, Zhicheng; Zhong, Hongzheng; Zhi, Qingqing; Chen, Yinqiu; Zhang, JiaHao; Li, Zhibiao; Lu, Zechao; Liu, Can; Tang, Fucai; He, Zhaohui; Sun, Xuan (Frontiers in Nutrition, 2024)
Background: Kidney stone disease (KSD) is a widespread problem in urology. But the associations between the Geriatric Nutritional Risk Index (GNRI), an important indicator for assessing the nutritional status of elderly hospitalized patients, and KSD are understudied.: Utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007-2018, our study analyzed the correlation between the GNRI and KSD prevalence at cross-sectional level. The aim of the study was to explore the association between GNRI and the prevalence of KSD to identify potential risk factors and inform prevention and management strategies for KSD. Methods: This cross-sectional study analyzed data focusing on 26,803 adults (20-80 years) after screening for complete data. It evaluated GNRI, a formula involving albumin, present, and ideal body weight, stratifying participants into quartiles. The primary outcome was the history of KSD, based on self-reports. Covariates included demographic, health, and lifestyle factors. Statistical analysis employed t-tests, ANOVA, Wilcoxon, and Kruskal-Wallis tests, with logistic regression modeling GNRI's impact on KSD prevalence, assessing odds ratios and potential multicollinearity, and sensitivity analyses excluding individuals with low eGFR and adjusting cycle years.Results: Significant disparities are found in GNRI distributions between individuals with and without kidney stones. Higher GNRI levels are more common in kidney stone patients, with 39.249% in the highest quartile versus 33.334% in those without stones. Notably, those in the highest GNRI quartile (Q4) show a lower prevalence of kidney stone disease (KSD) than those in the lowest (Q1), with rates of 11.988% versus 8.631% respectively (P < 0.0001). Adjusted model results reveal that higher GNRI quartiles (Q3-Q4) correlate with reduced KSD prevalence, with odds ratios of 0.85 (95% CI [0.72, 1.00]) and 0.76 (95% CI [0.65, 0.89]). A nonlinear inverse relationship exists between GNRI levels and KSD prevalence across the population (P < 0.001), confirming that higher GNRI lowers KSD prevalence. Subgroup and sensitivity analyses support these findings.The study underscores a significant, albeit nonlinear, association between elevated GNRI levels and decreased KSD prevalence. This relationship highlights the importance of nutritional assessment and management in KSD prevention strategies.